Effects of melengestrol acetate (MGA) on performance and carcass quality of feedlot heifers - J.T. Fox; M.F. Spire; T.J. Kessen; M.J. Sulpizio; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2002)
Sixty yearling heifers (827 lb initial body weight) were fed finishing diets an average of 95 days. To eliminate social interaction and riding, they were fed in individual pens. Diets were formulated using steam-flaked corn and alfalfa hay. Thirty of the heifers were given 0.5 mg/head daily of MGA. Feed intakes, daily gains, and feed efficiencies were not significantly affected by MGA. However, heifers fed MGA had a greater percentage of carcasses grading USDA Prime and Choice. There also was greater incidence of USDA yield grade 3 and 4 carcasses with MGA supplementation. MGA generally increased fat deposition, but had no significant effect on feedlot performance of individually fed heifers.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Melengestrol acetate (MGA); Performance; Carcass quality; Finishing heifers